Pengembangan Aplikasi Mobile "Petik BM" Layanan Pemeliharaan Jalan Kementrian PUPR Lampung - Aditya Bagas Pratama; Nurudin Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The Ministry of Public Works and Public Housing of Republic of Indonesia Lampung branch do their job in refer to the road performance indicator. Along with the time, their job did not correspond in reality on field and shows that the road service level has not fulfilled and the practice of the road performance indicator had not implemented maximally. After the contract had been signed and check the design, it is different on field. This thing results in the money and the time that they have to do to re-negotiate through technical justification. Other than that, low control to the job by the service provider and the customer should be gone to prevent the problems came back every year. The problems got more affected by the unprofessional manner by the quality control unit that stand under the Superintended General. Following up from that, so therefore needed an extra instrument in the controlling area to fulfill the road service level and the road performance indicator. This instrument had to be an extra tools in the form of an application that is used by Satker (Satuan Kerja) and PPK (Pejabat Pembuat Komitmen) to push the level of road service. The road performance indicator is the benchmark for the success of fulfilling the level of road service correspond to terms and condition apply. This development build with a method with 7 steps that starts at literature studies then requirement analysis, the planning process, implementation, testing, analysis of testing results, and end with drawing out the conclusion. Black Box Testing with validation methods is used in this development and the results of this development is Petik BM application where The Ministry of Public Works and Public Housing of Republic of Indonesia Lampung branch claims that this application fastened their job in maintaining the road.